Democracy As Culture : Deweyan Pragmatism in a Globalizing World. - Tan, Sor-hoon (State University of New York Press, 2008)
"Using a multidisciplinary approach, contributors to this volume explore the significance of John Dewey's Pragmatism for the contemporary world. They examine such issues as whether Classical Pragmatism justifies global democracy, whether Dewey's idea of democracy - so intimately linked to American culture - has any relevance for other cultures, and whether democracy can take other forms than those found in Europe and America. Contributors focus on Dewey's cross-cultural experience and affinities with Descartes and modern Neo-Confucians to provide a glimpse of how Dewey's influence outside America has stimulated other cultures, heralding a new stage in the growth of Pragmatism."--Jacket.